A general equilibrium model of environmental option values - Katsuyuki Shibayama; Iain Fraser (University of Kent, School of Economics, 2011)
In this paper we consider the option value of the environment employing a general equilibrium growth model with a stochastic technology. In our model, as in existing studies, because of irreversibility, the environment has significant real option value. However, unlike the existing literature in which the uncertainty of the value of the environment is given exogenously, the value of the environment is endogenously determined. In our model, the elasticity of substitution between the environment and consumption plays a crucial role. We show that the option value, and hence, the optimal decision are both affected by not only quantitatively but also qualitatively.
Keywords: G13; Q31; 330; real option values; environment; general equilibrium; elasticity of substitution